GaOOH Crystallite Growth on Liquid Metal Microdroplets in Water Influence of the Local Environment - Gan, Tiansheng (Langmuir : the ACS journal of surfaces and colloids, 2022)
Gallium-based liquid metals form alloys with a melting point close to or below room temperature. On the surface of these liquid metals, a thin oxide skin is formed once in contact with oxygen, and this oxide skin can be leveraged to stabilize liquid metal micro- and nanodroplets in a liquid. During sonication and storage of these droplets in aqueous solution, gallium oxide hydroxide (GaOOH) forms on these droplets, and given enough time or treatment with heat, a full shape transition and dealloying are observed. In this article, we show that GaOOH can be grown at room temperature and that the growth is dependent on both the local environment and temperature. GaOOH growth on liquid metal microdroplets located at the air/water interface is considerably faster than in the bulk phase. Interestingly, hydrolysis to GaOOH is hampered and stops at 15 °C in bulk water after 6 h. In contrast, hydrolysis commences even at 15 °C for liquid metal microdroplets located at the air/water interface, and full surface coverage is obtained after around 24 h (compared to 12 h at 25 °C at the air/water interface). The X-ray photoelectron spectroscopy (XPS) measurement suggests that gallium oxide is dissolved and Ga(OH)3 is formed as a precursor that reacts in a downstream reaction toward GaOOH. This improved understanding of the GaOOH formation can be leveraged to control the liquid metal micro- and nanodroplet shape and composition (i.e., for biomedical applications)